Faktor-Faktor yang Berhubungan dengan Self Management pada Pasien DM Tipe II - Sari Wahyuni Mustarim; Busjra M. Nur; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to identify the factors associated with self-management of type II DM patients in Kendari City. The study design was cross sectional. The results showed a significant relationship between DM knowledge, self-efficacy, family support, motivation and emotional aspects with self management (p <0.05). The factors that have the most significant relationship with self management are knowledge, self-efficacy and socioeconomic. Respondents who had self-efficacy had 102 times the opportunity to implement DM self-management better than those who lack self-efficacy (Ex (b) = 102,359). Whereas respondents who got good knowledge had 44 times the opportunity to implement good self management compared to those who lack knowledge. Conclusion, there is a significant relationship that is knowledge, self-efficacy and social economy with self management and the results of this study can be a reference for nurses to provide counseling about the importance of doing good self management. Keywords: DM Type II, Self Management